Development of Lipid-Based Nanocarriers for Increasing Gastrointestinal Absorption of Lupinifolin - Musika, Jidapa; Chudapongse, Nuannoi (Planta Medica, 2020)
Lupinifolin, a plant flavonoid, has been reported to possess various pharmacological effects. It most likely exerts low oral bioavailability because of poor water solubility. The objective of this study was to develop lipid nanocarriers as drug delivery systems to increase the gastrointestinal absorption of lupinifolin extracted from Albizia myriophylla. Three types of nanocarriers, lupinifolin-loaded solid lipid nanoparticles, lupinifolin-loaded nanostructured lipid carriers, and lupinifolin-loaded nanoemulsions, were prepared by an emulsification-sonication technique. All three types of nanocarriers loaded with lupinifolin, lupinifolin-loaded solid lipid nanoparticles, lupinifolin-loaded nanostructured lipid carriers, and lupinifolin-loaded nanoemulsions, were successfully synthesized. The lipid components chosen to formulate nanocarriers were tripalmitin and/or medium chain triglyceride. Physicochemical characterizations along with releasing profiles of lupinifolin-loaded lipid nanocarriers were compared. It was found that the best lipid nanocarrier for lupinifolin was lupinifolin-loaded nanostructured lipid carriers, which demonstrated the particle size of 151.5 ± 0.1 nm, monodispersity distribution with a polydispersity index of 0.24, negative surface charge at − 41.2 ± 0.7 mV, high encapsulation (99.3%), and high loading capacity (5.0%). The obtained lupinifolin-loaded nanostructured lipid carriers exhibited prolonged release in a simulated circulatory system but produced a low release in gastrointestinal conditions (3.7%). Intestinal permeability of the nanocarriers was further evaluated in everted intestinal sacs. The results from the ex vivo study indicated that lupinifolin-loaded nanostructured lipid carriers significantly increased the absorption of lupinifolin compared to the native form. In conclusion, lupinifolin-loaded lipid nanocarriers were successfully formulated as delivery systems to enhance its oral bioavailability. Further in vivo experiments are needed to validate the results from this study.
Keywords: lupinifolin; Albizia myriophylla; lipid nanocarriers; bioavailability; intestinal absorption; Leguminosae